The problems of genocide permanent security and the language of transgression - Moses, A. Dirk 1967- (Human rights in history, 2021)
Genocide is not only a problem of mass death, but also of how, as a relatively new idea and law, it organizes and distorts thinking about civilian destruction. Taking the normative perspective of civilian immunity from military attack, A. Dirk Moses argues that the implicit hierarchy of international criminal law, atop which sits genocide as the 'crime of crimes', blinds us to other types of humanly caused civilian death, like bombing cities, and the 'collateral damage' of missile and drone strikes. Talk of genocide, then, can function ideologically to detract from systematic violence against civilians perpetrated by governments of all types. The Problems of Genocide contends that this violence is the consequence of 'permanent security' imperatives: the striving of states, and armed groups seeking to found states, to make themselves invulnerable to threats